2015
DOI: 10.1111/ejn.12921
|View full text |Cite
|
Sign up to set email alerts
|

Action observation with kinesthetic illusion can produce human motor plasticity

Abstract: After watching sports, people often feel as if their sports skills might have been improved, even without any actual training. On some occasions, this motor skill learning through observation actually occurs. This phenomenon may be due to the fact that both action and action observation (AO) can activate shared cortical areas. However, the neural basis of performance gain through AO has not yet been fully clarified. In the present study, we used transcranial magnetic stimulation to investigate whether primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“…In considering a previous study by Nojima and colleagues [ 22 ], which found behavioural improvements after AO to be dependent on and positively correlated to the degree of kinaesthetic illusion elicited by the AO, it is conceivable that our MIR condition failed to induce a significant enough kinaesthetic illusion in the untrained hand such that this condition failed to elicit performance gains that were superior to those observed in the other feedback groups. One of the potential limitations to the conclusions drawn from the current study is the substantial inter-participant variability observed with respect to performance, both prior to, and following motor training, possibly suggesting a high degree of task complexity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In considering a previous study by Nojima and colleagues [ 22 ], which found behavioural improvements after AO to be dependent on and positively correlated to the degree of kinaesthetic illusion elicited by the AO, it is conceivable that our MIR condition failed to induce a significant enough kinaesthetic illusion in the untrained hand such that this condition failed to elicit performance gains that were superior to those observed in the other feedback groups. One of the potential limitations to the conclusions drawn from the current study is the substantial inter-participant variability observed with respect to performance, both prior to, and following motor training, possibly suggesting a high degree of task complexity.…”
Section: Discussionmentioning
confidence: 87%
“…Three groups of participants practiced a fast-as-possible two-ball rotation task with their dominant hand while receiving different types of visual feedback. For a better pictorial representation of how the two balls were rotated within the palm, please refer to Fig 1A out of the Materials and Methods section of Nojima and colleagues [ 22 ]. Participants in the Active Vision (ACT: n = 20, females: 14, mean age = 28.3 years, SD = 8.2 years) and Passive Vision (PAS: n = 20, females: 15, mean age = 25.8 years, SD = 6.3 years) groups focused on the active (training) or inactive (non-training) hand, respectively, while vision of the opposite (unattended) hand was occluded with a custom built stand.…”
Section: Methodsmentioning
confidence: 99%
“…In line with this finding, a recent study described a positive correlation between the performance gain and the vividness of the illusion induced by observing a movie clip showing a hand's motor task on a monitor placed over the participant's hand only when the relative positions of the displayed and the real hand were congruent (Nojima et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, research over the past decades has recognized that sensory feedback and mental imagery play a significant role in the learning process (Nyberg et al, 2006;Sigrist et al, 2013;Wolpert et al, 2011). In the case of vision, it has been shown that even in the absence of physical training, mere observation of someone else performing a motor task is sufficient to introduce significant gains in subsequent performance of the observer Cross et al, 2009;Kelly et al, 2003;Mattar and Gribble, 2005;Nojima et al, 2015;Vogt and Thomaschke, 2007;Ossmy and Mukamel, 2016). Furthermore, passive limb movement has also been shown to facilitate learning (Beets et al, 2012;Darainy et al, 2013;Vahdat et al, 2014;Wong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%